2020
DOI: 10.1016/j.ipej.2020.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Serum angiotensin converting enzyme, Erythrocyte sedimentation rate and high sensitive-C reactive protein levels in diagnosis of cardiac sarcoidosis- where do we stand?

Abstract: Background Cardiac sarcoidosis (CS) is increasingly being recognized in the last two decades. The diagnosis of CS depends on clustering of multiple symptoms, investigations and demonstration of a non-caseating granuloma on histopathology. Serum Angiotensin Converting Enzyme (SACE) level, one of the serological markers, is often elevated in systemic sarcoidosis. However, the yield of SACE level among patients with isolated or predominant CS is unclear. We conducted a retrospective study to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Some studies have reported a higher incidence of leukopenia and lymphopenia in patients with sarcoidosis [36,37]. Additionally, other studies have demonstrated significantly higher levels of RDW [38,39], PLR [40,41], NLR [12,42], MPV [24,42], CRP [13,43] and ESR [43] in patients with sarcoidosis compared to healthy subjects. A review published in 2019 identified soluble interleukin-2 receptors, CRP, serum amyloid A, and chitotriosidase as the most effective markers for confirming sarcoidosis (highest sensitivity), while angiotensin-converting enzyme (ACE), gammaglobulins, and lysozyme exhibited the highest specificity values for ruling out sarcoidosis [13].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported a higher incidence of leukopenia and lymphopenia in patients with sarcoidosis [36,37]. Additionally, other studies have demonstrated significantly higher levels of RDW [38,39], PLR [40,41], NLR [12,42], MPV [24,42], CRP [13,43] and ESR [43] in patients with sarcoidosis compared to healthy subjects. A review published in 2019 identified soluble interleukin-2 receptors, CRP, serum amyloid A, and chitotriosidase as the most effective markers for confirming sarcoidosis (highest sensitivity), while angiotensin-converting enzyme (ACE), gammaglobulins, and lysozyme exhibited the highest specificity values for ruling out sarcoidosis [13].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, ESR changes can be invoked as a criterion to judge the severity of myocardial inflammation and ischemia. 20 Fibrinogen, an acute reactive protein secreted by liver synthesis, boasts the highest concentration of coagulation proteins. Fibrinogen can be converted to fibrin under the action of thrombin, accelerating the formation of thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…Another study shows that the yield of elevated serum ACE levels is significantly lower and that ESR and hs-CRP are more sensitive markers for diagnosis at initial presentation of sarcoidosis, although not specific. 8 In certain parts of the world, Lyme's disease and Chagas disease are important causes of AV block in young adults. In India, these diseases are almost unknown.…”
Section: Discussionmentioning
confidence: 99%